Fever induced by fluorine-containing lubricant on stainless steel tubes. Issue 3 (August 1980) - Akesson, B; Högstedt, B; Skerfving, S
Abstract : Three subjects, all smokers, handling stainless steel tubes suffered repeated attacks of general malaise, chills, and fever lasting for several hours, mainly after gas soldering. Provocations by rubbing smoking tobacco against a tube produced similar attacks, and leucocytosis, after a few hours. The presence of fluorine on the tubes and in the febrifacient tobacco was shown. A fluorocarbon polymer lubricant was suspected of causing the attacks. Heating (1000 degrees C) of the tubes eliminated the effect.